'"The less deceived": subjectivity, gender, sex and love in Sylvia Plath's and Philip Larkin's poetry - Alita Fonseca Balbi (2012)
In this thesis, I make a comparative reading of Philip Larkin's and Sylvia Plath's poetry. The focus of the reading is on how their works discuss subjectivity and interpersonal relations. The analysis takes into consideration three main concepts: subjectivity, gender and love. First I establish a definition of the term subjectivity for the purposes of this analysis, and then compare and contrast the ways in which Larkin's and Plath's poems depict it. I also explore how gender roles are conveyed in their poetry as preconceptions imposed on people, and how these impositions affect in negative ways the relationships between women and men. The third concept, love, is discussed in light of the possibility of the subject to establish more profound emotional connections with the outer world and with others. Such emotional connections are often portrayed as inspiring the speakers poetic sensibility because they allow them to perceive the world in more subjective terms. I argue that both Larkin's and Plath's poetry depict speakers with conflicting views on subjectivity: at the same time they are aware of the constructed nature of social roles, they also believe in a romantic inner self. Even though their works portray social norms and gender roles as deceiving, their speakers still long for more positive deceptions such as friendship and love. For this reason, their speakers are named in this thesis the less deceived, a reference to one of Larkin's poems. In the poems analyzed, being the less deceived has an ambiguous meaning, conveying both positive and negative aspects. While it reflects the speakers awareness of the manipulative paradigms that underlie social interactions, it also shows a feeling of deprivation because of the discredit that falls upon transcendental matters such as religious faith and love, both of which are deceits that the poetic voices long for. Being the less deceived also refers to the fact that knowing the manipulative character of social norms does not mean they are free from it. Instead, the majority of the speakers in Larkins and in Plaths poetry still find themselves entrapped in meaningless social rites and are incapable of changing the society which they try to be, and at the same time avoid being, a part of.